Challenge and Opportunity of Mobile Banking in Afghanistan - Naseri, Mohammad Fahim; Frugh, Qurban Ali; Shamsi, Qamaruddin (Universitas Dinamika, 2025)
Mobile banking is a major advancement in information technology, transforming the banking system by enabling users to conduct transactions anytime, anywhere. In Afghanistan, it was first introduced in 2017 by Azizi Bank, leading the way in accessible banking. However, several challenges remain. This study examines the challenges and opportunities of mobile banking in Afghanistan using a mixed-methods approach. Data was collected through surveys and interviews. Findings show that only 12% of respondents see mobile banking as secure and convenient, while 88% express concerns over cybersecurity risks, network reliability, weak internet infrastructure, unstable income, and lack of trust in banking services. The study also highlights key barriers such as low digital literacy, regulatory challenges, limited infrastructure, low income levels, public distrust after political transitions, and poor internet access. Despite its potential, overcoming regulatory, infrastructural, and socio-economic challenges is crucial for the growth of mobile banking in Afghanistan. The result is mobile banking in Afghanistan is currently facing major problems that investment in this sector has not been made and what is needed, mobile banking services in Afghanistan have not grown.